SPEI encounter histories - Christie, Katherine; Hollmen, Tuula; Flint, Paul; Douglas, David (Dryad Digital Repository, 2018)
The data file contains encounter histories for Spectacled Eiders captured on Kigigak Island, Alaska from 1992-2015.